Social Power: The Gap Between Majority and Minority Groups in Martin Luther King Jr.’S Speeches - Sylvia Christy Hendarto (Ma Chung Press, 2019)
This study examines the social power between majority and minority group as represented in Martin Luther King Jr.’s speeches. It investigates social power further into types of social power used, and how the gap between majority group and minority group is reflected in the speeches. Critical discourse analysis with socio cognitive approach was applied. The data were taken from three speeches of Martin Luther King Jr.: “I Have a Dream”, “Our God is Marching On”, and “I’ve Been to the Mountaintop”. The result revealed that there were several types of social power appeared in the speeches. The finding on the gap between majority and minority group is reflected in their social status and roles in society.